Pengembangan Business Process Improvement Sistem Pelayanan Kesehatan Lingkungan Dan Klinik Menggunakan Zachman Framework (Studi Pada UPT. Laboratorium Dinas Kesehatan Kota Malang) - Hari Yogi Vernando; Yusi Tyroni Mursityo; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Health Department Laboratory is Technical Implementation Unit in health sector under the auspices and responsibility of Malang city health office. Health department laboratorie has duties and functions to provide health testing services. In running of the business process there are several problems that potential disrupt the course of business activities, one of the problems is the running time of the process is too long and non-optimal. The non-optimal processes in the health laboratory include data storage, the data is not integrated or fragmented that can be a cause of data duplication, and data loss due to human error. So it is necessary to analyze the business processes that have been applied, then evaluated it to determine the business processes that potential disrupt the course of organizational activities in order to provide advice in the form of recommendations for business process improvement and design of a system. This study uses Business Process Improvement (BPI) as an evaluation method, and system design using Zachman Framework. This research uses 3 perspectives from 6 perspectives on the Zachman Framework, and uses the first 3 phases of Business Process Improvement. Testing is done after the design and evaluation of business processes. The testing is uses bizagi simulation and the system testing using blackbox. This research produces the proposed business process as well as system design.